EXPLORING THE CORRELATION OF SOCIOLINGUISTIC COMPETENCE AND SPEAKING PROFICIENCY, AND HOW LEARNERS PERCEIVED THEM - Fariha, Nur; Anwar, Khoirul; Maruf, Nirwanto (English Review: Journal of English Education, 2023)
This study aims to explore the correlation between sociolinguistic competence and speaking proficiency in language learners while examining their perceptions of these aspects. Conducted using a mixed-methods approach, the research gathered data from 65 participants across multiple universities in Lamongan Regency, East Java, Indonesia. Quantitative analysis involved Test of English as a Foreign Language (TOEFL) scores, structured surveys, and questionnaires assessing sociolinguistic competence. Qualitative insights were obtained from in-depth interviews, illuminating participants' experiences, beliefs, and challenges in diverse social settings related to language use. Quantitative findings indicate a strong correlation between sociolinguistic competence and speaking proficiency. The Pearson correlation coefficient for "Sociolinguistic Competence" was 1.000, confirming a perfect positive correlation, while the correlation between "Sociolinguistic Competence" and "Speaking Proficiency" was .688, signifying a robust positive correlation. Similarly, "Speaking Proficiency" exhibited a .688 correlation with sociolinguistic competence. Qualitative insights emphasized themes such as sociolinguistic norms, language preferences, and challenges in communicative contexts. Participants stressed the importance of adhering to sociolinguistic norms, showcased preferences for specific language styles in diverse contexts, and highlighted challenges in multilingual environments. The study solidifies the significant correlation between sociolinguistic competence and speaking proficiency among participants, emphasizing the pivotal role of sociolinguistic competence in enhancing speaking proficiency. These outcomes stress the reciprocal influence between these dimensions in language learning, emphasizing the need for tailored language learning strategies incorporating sociocultural dimensions. Future research may delve into implementing sociolinguistic approaches in language education to enhance learners' communicative skills and sociolinguistic awareness.